1974
DOI: 10.1137/0203021
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Related Problems

Abstract: Abstract. We look at several problems from areas such as network flows, game theory, artificial intelligence, graph theory, integer programming and nonlinear programming and show that they are \. related in that anyone of these problems is solvable in polynomial time iff all the others are, too. At i present, no polynomial time algorithm for these problems is known. These problems extend the equivalence class of problems known as P-Complete. The problem of deciding whether the class of 1 languages accepted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(129 citation statements)
references
References 6 publications
1
126
0
2
Order By: Relevance
“…First, quadratic bounds are computed based on linear bounds (or condition numbers). Second, we observe that the constraint kỹk ¼ 1 in Problems (4) and (5) Alternatively, we can show that computing quadratic bounds is in the complexity class of functional NP [23].…”
Section: Quadratic Perturbation Boundmentioning
confidence: 82%
“…First, quadratic bounds are computed based on linear bounds (or condition numbers). Second, we observe that the constraint kỹk ¼ 1 in Problems (4) and (5) Alternatively, we can show that computing quadratic bounds is in the complexity class of functional NP [23].…”
Section: Quadratic Perturbation Boundmentioning
confidence: 82%
“…As mentioned in Section 1, Sahni [16] showed that the maximum integer equal flow problem is NP-hard. Later, Garey and Johnson [10] observed that the modification of a construction by Even et al [7] shows that the problem is NP-hard even if the capacity of every arc is 1.…”
Section: Problem Definitionmentioning
confidence: 94%
“…The equal flow problem was first studied by Sahni [16] as a generalization of the traditional network flow problem. Its setup is similar to a standard maximum flow problem: we are given a directed graph G = (N, A) with capacities u a for all a ∈ A, and a designated source node s and sink node t. In addition, we are also given sets R 1 , R 2 , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies made by Karp and successively those of Sahni [5] and Ullman [7] have more and more enlarged this équivalence class which constitutes the top of complexity for the NP-problems.…”
Section: Introductionmentioning
confidence: 99%